2019
DOI: 10.1002/anie.201903717
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reproducible Formation of a Polymer Single‐Molecule Junction for a Well‐Defined Current Signal

Abstract: Single-molecule devices attract much interest in the development of nanoscale electronics.A lthough av ariety of functional single molecules for single-molecule electronics have been developed, there still remains the need to implement sophisticated functionalization towardp ractical applications. Given its superior functionality encountered in macroscopic materials,apolymer could be au seful building blocki nt he single-molecule devices.T herefore,amolecular junction composed of polymer has nowb een created. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“… 21 The molecular bridging in the junction structure causes the current increase, while the junction breakdown results in the decrease in the current to the initial set-point value. The plateaus were detected by adaptive threshold analysis (ATA), 24 which analyzes the I – t traces based on a recursive low-pass filtering function. 5 A two-dimensional (2D) histogram shows that the statistically most probable plateau appears at 1.3 mG 0 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 21 The molecular bridging in the junction structure causes the current increase, while the junction breakdown results in the decrease in the current to the initial set-point value. The plateaus were detected by adaptive threshold analysis (ATA), 24 which analyzes the I – t traces based on a recursive low-pass filtering function. 5 A two-dimensional (2D) histogram shows that the statistically most probable plateau appears at 1.3 mG 0 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The capture and release states of individual molecules are detected in the I(t ) captures as a telegraphic signal that oscillate between two levels. 6,13,14,29,30,32,34 One level is related to the low-current regime (Fig. 1, scenarios I, III and V) when the molecule releases from one or both electrodes (tip and substrate) and hence only background (tunnelling) current is detected (I REL ).…”
Section: Resultsmentioning
confidence: 99%
“…It enables unbiased data processing and explores the complete junction formation and release mechanism beyond the conventional focus on SM capture current signatures only. [29][30][31][32] We have found that the nearfield optomechanical effects alter the kinetics of both, the SM capture and release process as well as the free-energy capture and release profiles. On the one hand, the presence of the nearfield increases the rate constant of the capture while it decreases the one of the release process exponentially with the nearfield strength.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that multidentate binding to the electrodes enhances the stability of the junction, resulting in a longer junction lifetime τ. 36 Hence, we anticipate that the τ-based classification proposed above can be extended to differentiate singly and multiply phosphorylated peptides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%